Corporate Social Responsibility in the Age of Sustainability: A Global Perspective on Management Practices - Reni; Mochamad Rizki Sampoerno; Fauzie Pari; Rizki Chrisulianti (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR) on sustainability practices in Indonesian companies. Employing a quantitative approach with multiple linear regression methods, the research involves data from 100 respondents across various industrial sectors, all holding strategic roles in their companies' CSR management. The independent variables consist of four CSR dimensions: economic, legal, ethical, and philanthropic, while the dependent variable is sustainability practices, which encompass environmental, social, and governance aspects. The results show that all CSR dimensions simultaneously have a significant impact on sustainability practices, with a coefficient of determination (R²) of 0.681 and a significance value of 0.000. The economic dimension emerges as the most dominant factor, having the highest regression coefficient. Meanwhile, the ethical and philanthropic dimensions, although less dominant, remain significant and play important roles in building social legitimacy and corporate reputation. This study also emphasizes the importance of integrating CSR into long-term business strategies, as well as the need for digitalizing sustainability reporting and establishing dedicated sustainability management units. The findings contribute theoretically to the development of a strategic CSR model and offer practical implications for corporate management in addressing global sustainability demands.